Customization in location-based advertising: Effects of tailoring source, locational congruity, and product involvement on ad attitudes. - Lee, Sangmee; Kim, Ki Joon; Sundar, S. Shyam (Computers in Human Behavior)
This study explores the psychological effects of information tailoring, locational congruity, and product involvement on user attitudes toward location-based advertising (LBA) on mobile devices. Results from a 2 (type of information tailoring: personalization vs. customization) × 2 (level of locational congruity: high vs. low) × 2 (level of product involvement: high vs. low involvement) between-subjects experiment ( N = 115) showed that customization and locational congruity were effective strategies for inducing positive attitudes about LBA and its service quality. In addition, the ad’s perceived intrusiveness was found to mediate the effects of product involvement on participants’ attitudes toward LBA. Implications of the findings are discussed.